Adaptive Coordinated Variable Speed Limit between Highway Mainline and On-Ramp with Deep Reinforcement Learning - Ming Cheng; Chenghao Zhang; Hui Jin; Ziming Wang; Xiaoguang Yang (Journal of Advanced Transportation)
Highway merging bottleneck is challenged with serious traffic conflicts between on-ramp and mainline vehicles, causing significant capacity drop and drastic speed changes. The paper proposes an adaptive coordinated variable speed limit model to manage highway speed of on-ramp and mainline continuous sections without priority to mainline. That helps to remove the speed difference between the vehicles from on-ramp and mainline flooding into the merging zone, and to sustain actual traffic density close to critical density to counteract capacity drop as indicated with macroscopic fundamental diagram. The method of deep reinforcement learning based on deep deterministic policy gradient is employed to solve the proposed model with a row of continuous control variables. Simulation platform with VISSIM 5.3 is established, and the proposed method can enhance traffic flow through the merging zone by around 10% and 19% under static and dynamic demand, respectively, in addition to reduced density and speed variation by around 30%. This research provides insights into the management of highway capacity so as to secure traffic efficiency and reliability for the merging zone.